KONTRADIKSI IDENTITAS PADA AKOMODASI KOMUNIKASI BUDAYA DALAM IKLAN MARJAN VERSI BELA DIRI 2011 - Yesica Yuliani Clara; Laurencia Steffanie Mega Wijaya Kurniawati (Jurnal Komunikasi, 2024)
Cultural differences are not always acceptable in society, there is a dominant culture that makes other cultures feel alienated. The lack of people's ability to understand cultural diversity raises issues of intercultural communication, one of the issue is stereotypes about cultures of one another also etnosentrism. In cultural differences, it requires people to adapting new cultures, which is appears in the Marjan Syrup Advertisements on the month of Ramadan in 2011 Martial Art Version entitled "Silat HipHop Kakek-Cucu (Grandfather-Grandson) Dance" lasted 2 minutes 24 seconds. The differences between two cultures, namely western culture (Hip- Hop) and Betawi culture (Pencak Silat) which is described in the Marjan advertisement, The research is focuesed on the process of accommodation of the two figures, namely the grandfather as a silat teacher (Betawi Culture) and grandchildren who are skilled in hip hop dancers (Western Culture), in conducting accommodation communication related to the contradictions between their cultural identities. This study aims to uncover cultural acculturation as an enrichment of Indonesian cultural identity uses a quantitative approach with a content analysis method. The results of communication accommodation in intercultural interaction between the two figures indicate the existence of modification, adjustment, or regulating one's behavior when responding to the communication and behavior of others